CHILD’S COGNITIVE MATURITY THROUGH MULTIMEDIA NOWADAYS - Hafizudin; Saridah, Siti (Journal of English Education and Teacher Trainer, 2024)
This paper focuses on analyzing the child’s cognitive maturity through multimedia nowadays. It portrays two main topics namely: (1). The current development of a child's cognitive maturity and (2). The impacts of multimedia on a child's cognitive maturity. The grand theory used is the personal psychology of development. The theory specifies on the difference between millennial and alpha-betha generations on its psychological developments. By using library study, the researchers conduct a deep analysis about these developments. The result shows that there is a child’s cognitive maturity after intensively using multimedia. The most realistic reason is it provides the learners no awareness in learning by default and enjoys delightful displays. Using multimedia in childhood learning accelerates a child's cognitive growth such as spatial cognitive, representative cognitive, iconic skills, problem solving, stimulating attention to the material and perception.